Pendidikan Kesehatan Berbasis Budaya pada Orang dengan Diabetes Mellitus: Sebuah Scoping Review - Nurfadhila Nurfadhila; Kusrini Semarwati Kadar; Takdir Tahir (LPPM Hang Tuah Pekanbaru, 2023)
Self-management health education is considered an important element of treatment for all people with diabetes and those at risk of developing T2DM. A wide variety of diabetes self-management education (DSME) interventions are available in high-attenuation countries, whereas limited information on culture-based health education exists in Asian countries. The purpose of this scoping review is to map culture-based health education in terms of strategies, outcomes, and action interventions to improve health outcomes and adherence of people with diabetes mellitus. The PRISMA (preferred reporting items for systematic review and meta-analysis) method was used at all stages of the review. The databases used in this study were Medline (OVID), Pubmed, ProQuest, CINAHL, Scopus, Inform it Data, and Web of Science from 2010 to 2022. A manual search of the database yielded 197 pieces of data; 11 full-text included for review. Three forms of cultural integration in health education include using dual language (Spanish and English) ​​in the delivery of health education, creating guidelines books and questionnaires in local languages, and creating and modifying diabetes self-management programs or interventions that are adapted to local culture, for example by using food samples consumed. every day by the tribe. The conclusion of this study is that the development of family and culturally supported diabetes interventions integrated with health education is an integral part of maintaining self-management behavior and improving health outcomes for patients with T2DM.